Harnessing Indonesian Local Wisdom for Innovative Tourism Development in the Creative Economy - Zaini, Rafiq; Ismail, Kamariah (International Journal of Accounting and Management Research, 2024)
This concept paper investigates how Indonesian local wisdom can be incorporated into innovative tourism development in the context of creative economy. By conducting an in-depth literature review and analyzing various case studies, the research investigates diverse applications of local wisdom in tourism across Indonesia, examining economic impacts, cultural preservation efforts, and alignment with creative economy principles. The results reveal significant potential in utilizing cultural heritage to develop distinctive, environmentally friendly tourism experiences that support local communities and the national economy. The research highlight challenges in implementation, such as the risk of cultural exploitation and clashes between modernization and tradition and suggests methods for sustainable development. By blending the preservation of culture with economic advancement, Indonesia has the potential to become a pioneer in sustainable and culturally respectful tourism development, providing valuable insights for similar culturally diverse developing countries.